Methods in food analysis - Cruz, Rui M. S.; Khmelinskii, Igor; Vieira, Maria Margarida Cortez (CRC Press/Taylor & Francis Group, 2014)
This book reviews methods of analysis and detection in the area of food science and technology. Each chapter deals with determination/quantification analyses of quality parameters in food, covering topics such as lipids, color, texture, and rheological properties in different food products. The book focuses on the most common methods of analysis, presenting methodologies for specific work conditions. It provides a reference for food engineers and researchers working in the area of food science and technology as well as undergraduate and postgraduate students.